The rights of the child: knowledge and compliance - CARVALHO, Olívia; BORGES, Ana; Sónia GALINHA (Revista Jurídica Portucalense, 2024)
The Convention on the Rights of the Child - CRC -, adopted by the General Assembly of the United Nations – UN – on November 20, 1989, ratified by Portugal on September 21, 1990 Was a significant milestone in safeguarding and promoting children's rights throughout history. It is therefore essential that all those involved in civil society as a whole, encompassing the political sphere, and particularly entrusted with the direct responsibility of educating children, take every conceivable measures to ensure that these rights are guaranteed. The children themselves should also know when these rights are or are not being respected. This study aims to assess children’s awareness of the CRC and the extent to which their rights are being fulfilled. Furthermore, we aim to examine whether significant differences exist in the fulfilment of rights and their perception among children in the North, Center, and South of Portugal. A total of 123 teenagers ranging from 7th to 12th grade participated in this research. The students came from three different areas of the country: North, Center and South of Portugal. The survey "Being a Child with Rights - Convention on the Rights of the Child: Knowledge and Compliance" was applied as an instrument. The results indicate that many children continue to be disrespected in their rights.